Water Level Detector System Using Copper Wire Sensor - ZAILANI, MUHAMAD NORHAMIZAN (Enhanced Knowledge in Sciences and Technology, 2022)
The aim of this project is to design a water level detector system that can transmit and receive signals when the water reaches a certain level which is low level, normal level, and high level. The condition of the water level will be displayed on a light-emitting diode (LED). The motivation of this project is due to, the user or operator that always faces the difficulty to recognize the volume of water level in the tank. Therefore, the water level detector system is built to overcome the problems, especially in their residential areas such as apartments, flats, and condominiums, where the water storage tank is placed on the top of the building. In this project design of a water level detector, we are using a single strand wire as a pin detector that detects the water level. The piezoelectric buzzer is used to warn the operator, while a light-emitting diode (LED) is used to display the water level in the tank whether it is red which show the water level is thirty percent (30%) (Low Level), blue LED for the normal level (50%) and green LED if the water level is hundred percent (100%) (High Level). To run this project design, we will be using Arduino UNO as coding and will be written in Arduino Integrated Development Environment (IDE). With this system, the operator will be more alert with the water status in the tank and can avoid the water tank from empty or overflowing. This indirectly can also avoid any storage water tank accidents that are related with many types of factors such as maintenance error, operational mistake, sabotage, failure of equipment, crack, leak, etc. In this project design, we will find the parameter of voltage at each sensor when it reacts with the water. All sensors will have different voltage values.